Creating Beauty: The Experience of a Fashion Collection Prepared by Adolescent Patients at a Pediatric Oncology Unit. Issue 6 (November 2015) - Veneroni, Laura; Clerici, Carlo Alfredo; Proserpio, Tullio; Magni, Chiara; Sironi, Giovanna; Chiaravalli, Stefano; Roncari, Luisa; Casanova, Michela; Gandola, Lorenza; Massimino, Maura; Ferrari, Andrea
Aims and Background: Adolescent patients with cancer need psychological support in order to face the traumatic event of cancer diagnosis and to preserve continuity with their normal lives. Creative projects or laboratories may help young patients express their thoughts and feelings. Methods: The Youth Project developed activities dedicated to adolescents to give them a chance to vent their creative spirit and express themselves freely. In the first project, the teenagers designed their own fashion collection in all its various stages under the artistic direction of a well-known fashion designer, creating their own brand name (B.Live), and organized a fashion show. Results: In all, 24 patients from 15 to 20 years old took part in the project. The fashion project proved a fundamental resource in helping the young patients involved to regain a positive self-image and the feeling that they could take action, both on themselves and in their relations with others. Conclusions: Facilitating the experience of beauty may enable hope to withstand the anguish caused by disease. This experience integrated the usual forms of psychological support to offer patients a form of expression and support during the course of their treatment.